Spatial patterns of urbanisation in Sub-Saharan Africa: A case study of Uganda - Tumwesigye, Samuel; Vanmaercke, Matthias; Hemerijckx, Lisa-Marie; Opio, Alfonse; Poesen, Jean; Twongyirwe, Ronald; Rompaey, Anton Van (Development Southern Africa, 2021)
Sub-Saharan Africa is rapidly urbanising. This urbanisation may contribute to socio-economic development as more people participate in the urban economy. Nevertheless, rapid urbanisation is not always sustainable. Primary cities often grow fast, leaving secondary towns lagging behind with weaker economies. Viable strategies for sustainable urbanisation may therefore also need to focus on developing secondary towns. Nevertheless, very few studies, hitherto, have assessed the (relative) importance of secondary towns in urbanisation process in Sub-Saharan Africa. We aim to address this gap by studying the patterns and explanatory factors of urban population growth in Uganda. Based on a longitudinal analysis of population ranksize distribution, we show that the population distribution gap between secondary towns and the primary city is widening. Nevertheless, statistical analyses further indicate that secondary towns with above 50 000 inhabitants have the highest population growth rates. This indicates that future investments should aim at upgrading socio-economic infrastructures in secondary towns.
Keywords: Sustainable urbanisation; Rank-size analysis; Secondary towns; Sub-Saharan Africa